Hubungan Ketersediaan Air Bersih dengan Kepemilikan Jamban Sehat di Dusun Panjing Desa Bandar Kabupaten Pacitan - Fiqi Nurbaya; Nine Elissa Maharani; Dewi Puspito Sari; Linda Fatika Sari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Initial survey with interviews and observations in 10 respondent houses found that each house still did not have a healthy toilet, the condition was poor, it gave off an unpleasant odor, the distance between the bathroom and the water source was 5-7 meters, and there was no roof or walls. Healthy toilets (30%) were owned by 3 respondents. Unhealthy toilets (70%) were owned by 7 respondents. Most people in Panjing Hamlet did not know the importance of having a healthy toilet. The research method used was cross-sectional. The sampling technique used was proportional stratified random sampling totaling 182 families. Data collection was carried out by observation and interviews. The research instrument used observation sheets and questionnaires. Data analysis used the chi-square test with a 95% confidence level. The variable of clean water availability was lacking by 51.1% or 93 respondents and sufficient water by 48.9% or 89 respondents. The variable of toilet ownership by 85.2% or 155 respondents did not meet the requirements and 14.8% or 27 respondents met the requirements. There is a significant relationship between the availability of clean water (p value: 0.009) and ownership of healthy toilets.